An Updated Model Does Not Reveal Sex Differences in Patellofemoral Joint Stress during Running - Laura Jacobson; C. Nathan Vannatta; Catherine Schuman; Thomas W. Kernozek (North American Sports Medicine Institute, 2022)
# Background Structure-specific loading may have implications in understanding the mechanisms of running related injury. As females demonstrate a prevalence of patellofemoral pain twice that of males, this may indicate differences in patellofemoral loads between males and females. Previous works investigating differences in patellofemoral joint stress have shown conflicting results, but the models employed have not used estimates of muscle forces or sex specific contact areas. # Hypothesis/Purpose The aim of this study was to examine sex differences in patellofemoral joint stress using an updated model to include estimates of quadriceps muscle force and sex-specific patellofemoral contact area. # Study Design Descriptive Laboratory Study # Methods Forty-five healthy recreational runners ran at a controlled speed down a 20-meter runway. Kinetic and kinematic data were utilized to estimate muscle forces using static optimization. Quadriceps muscle force was utilized with sex-specific patellofemoral joint contact area in a two-dimensional patellofemoral joint model to estimate patellofemoral joint stress. Multivariate tests were utilized to detect sex differences in patellofemoral loading and hip and knee kinematics. # Results No differences were found between sexes in measures of patellofemoral loading or quadriceps force. Females displayed a reduced knee extension moment and greater hip adduction and internal rotation than males. # Conclusion The inclusion of static optimization to estimate quadriceps muscle force and sex-specific contact area of the patellofemoral joint did not reveal sex differences in patellofemoral joint stress, but differences in non-sagittal plane hip motion were detected. Therefore, two-dimensional patellofemoral models may not fully characterize differences in patellofemoral joint stress between males and females. Three-dimensional patellofemoral models may be necessary to determine if sex differences in patellofemoral joint stress exist. # Level of Evidence 3b